Penggunaan learning.aljazeera.net sebagai motivasi belajar mahasiswa dalam meningkatkan maharah kitabah - Nidhom, Moch (Maliki Interdisciplinary Journal, 2025)
Currently, in the world of language education, various digital-based learning media can be found. One of the interesting digital media in language learning is Learning.aljazeera.net.To achieve learning objectives, in addition to the role of media as a tool to assist in successful learning, student motivation also needs to be considered. This research aims to determine the percentage of student motivation in the Kitabah II class using learning.aljazeera.net as a learning medium and its impact on kitabah proficiency.This research is a quantitative descriptive study. With the research subjects being 14 students from the 2021 cohort of the Arabic Language Education B class in the Maharah Kitabah course at Maulana Malik Ibrahim State Islamic University Malang. The researcher used a learning motivation questionnaire distributed to the research subjects via Google Form. The questionnaire was created based on the learning motivation indicators by Hamzah B Uno. The learning motivation indicators according to Uno, overall, the responses to all questions containing the learning motivation indicators show that learning.aljazeera.net can enhance students' learning motivation in improving their writing skills. Although there were some respondents who chose to be neutral due to learning styles or learning experiences that were not well-suited when using learning.aljazeera.com. The use of digital learning platforms such as learning.aljazeera.net can be considered an effective strategy in language learning, particularly in meeting learning needs and enhancing student motivation. These findings can serve as a reference for the development of other digital language learning platforms that can enhance students' motivation and skills in improving their Arabic language proficiency.